Acute Kidney Injury Following Multiple Wasp Stings: A Case Report with Complete Renal Recovery after Hemodialysis (Bangladesh Medical Journal, 2026)
Acute kidney injury (AKI) is a rare but serious complication of multiple wasp stings due to systemic envenomation. We report the case of a 55 year old male from rural Bangladesh who developed severe AKI following approximately 100 - 120 wasp stings (Vespa affinis). The patient initially presented with localized pain and swelling, followed by progressive oliguria and generalized edema. Laboratory evaluation revealed markedly elevated serum creatinine (19.2 mg/dL), hyponatremia, and metabolic derangement. In view of severe azotemia and persistent oliguria, hemodialysis was initiated. The patient underwent seven sessions of hemodialysis, resulting in gradual clinical and biochemical improvement. Serial laboratory findings demonstrated a progressive decline in serum creatinine, reaching near-normal levels (1.4 mg/dL) by day 114. This case highlights that AKI following wasp envenomation, although potentially life-threatening, is reversible with early recognition, timely referral, and appropriate renal supportive therapy.Bangladesh Med J. 2025 May; 54(2): 35-39